Alcohol consumption in men is influenced by qualitatively different genetic factors in adolescence and adulthood. Issue 9 (September 2013) - Edwards, A. C.; Kendler, K. S.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Alcohol consumption is influenced by genetic factors. Previous studies have examined the heritability of alcohol consumption, or related phenotypes, from adolescence into adulthood, frequently finding that total heritability changes over time. However, it remains unclear whether the same genes underlie liability to alcohol consumption across development versus whether novel risk genes become important over time. Method A population-based study of adult male twins (n=1790) born in Virginia, USA, retrospectively reported on their average monthly alcohol consumption from early adolescence through adulthood. We used twin modeling methods to explore genetic and environmental influences on alcohol consumption over time. Results One latent genetic factor accounted for the majority of the heritability in alcohol consumption during mid- to late adolescence, but its influence declined thereafter; from young adulthood forward, heritability was largely attributable to a second genetic factor. The total heritability of alcohol consumption increased from 0 at ages 12–14 years to 0.40 by ages 18–21 years. Shared environmental factors declined in influence over time. Conclusions The heritability of alcohol consumption over time is dynamic both quantitatively and qualitatively. These results have important implications for gene identification endeavors. Furthermore, these findings could inform efforts to elucidate developmentally dynamic behaviors, such as antisocial behavior.